KONSISTENSI PERENCANAANDAN IMPLEMENTASI PROGRAM PENDIDIKAN PADA SEKOLAH MENENGAH UMUM DI KABUPATEN POSO TAHUN 2007-2008 - , MAHARAJA BOTILANGI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study aims to describe the consistency between policy and implementation of educational program at General High School strata funded by APBD (Regional Budget) of 2007 and 2008. On the other hand, it also intends to explore the factors contributing to process in stating the priority scale of educational project. The study uses qualitative-descriptive method to describe the existing phenomena with the use of natural setting. Primary and secondary data collected through interviews, documentation and observation are used. The findings of the study suggest that the policy and implementation of educational program, when related to the achieved priority scale implemented in programs, are found not optimal or inconsistent. The factors contributing to process in stating the priority scale of educational program, among others, are rampant conflict of interests among the involved parties during the decision making for policies. The study concludes that educational policies prioritizing on expanding and equal distribution of quality educational service access for community elements in Poso District likely have not been optimally implemented. Particularly at General High School strata up to the period of 2005-2009, some sub-districts are found not to have sufficient educational infrastructures.